Childhood obesity from the genes to the epigenome - Sivakumar, Senthil; Lama, Dechen; Rabhi, Nabil (Frontiers in Endocrinology, 2024)
The prevalence of obesity and its associated comorbidities has surged dramatically in recent decades. Especially concerning is the increased rate of childhood obesity, resulting in diseases traditionally associated only with adulthood. While obesity fundamentally arises from energy imbalance, emerging evidence over the past decade has revealed the involvement of additional factors. Epidemiological and murine studies have provided extensive evidence linking parental obesity to increased offspring weight and subsequent cardiometabolic complications in adulthood.Offspring exposed to an obese environment during conception, pregnancy, and/or lactation often exhibit increased body weight and long-term metabolic health issues, suggesting a transgenerational inheritance of disease susceptibility through epigenetic mechanisms rather than solely classic genetic mutations. In this review, we explore the current understanding of the mechanisms mediating transgenerational and intergenerational transmission of obesity. We delve into recent findings regarding both paternal and maternal obesity, shedding light on the underlying mechanisms and potential sex differences in offspring outcomes. A deeper understanding of the mechanisms behind obesity inheritance holds promise for enhancing clinical management strategies in offspring and breaking the cycle of increased metabolic risk across generations.